2021
DOI: 10.1038/s41598-021-97907-y
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology in the mimetic higher-curvature $$f(R,R_{\mu \nu }R^{\mu \nu })$$ gravity

Abstract: In the framework of the mimetic approach, we study the $$f(R,R_{\mu \nu }R^{\mu \nu })$$ f ( R , R μ ν R μ ν … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…In the case of Scalar Tensor Fourth Order Gravity, we find that the parameters of the model are given by (see Eqs. (32,31,30)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Scalar Tensor Fourth Order Gravity, we find that the parameters of the model are given by (see Eqs. (32,31,30)…”
Section: Discussionmentioning
confidence: 99%
“…It must be mentioned that modifications of GR are also motivated by the fact that Einstein's theory of gravity breaks down in the UV [12,13]. Such deviations from General Relativity occurs in several frameworks, such as Brans-Dicke and scalar-tensor (ST) theories [14][15][16], braneworld theories [17][18][19][20][21][22], higher order invariants such as f (R) and f (φ, R, R 2 , R µν R µν , R) (which correspond to Einstein's gravity plus one or multiple conformally coupled scalar fields [23][24][25][26]) [27][28][29][30][31], noncommutative geometry [32], and compactified extra dimension/Kaluza-Klein models [33][34][35][36][37][38]. Moreover, they can also be generated from higher-order terms in the curvature invariants, nonminimal couplings to the background geometry in the Hilbert-Einstein Lagrangian [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for a spherically symmetric spacetime the only solution is the Schwarzschild spacetime which means that the Birkhoff's theorem is hold. Moreover, mimetic theory have been extended to f (R) gravity [54][55][56][57][58][59][60][61][62][63][64][65][66][67] and to Gauss-Bonnet gravitational theory [68][69][70][71][72]. More specifically, a unified scenario of early inflation and late-time acceleration in the framework of mimetic f (R) gravity was formulated in [73].…”
Section: Introductionmentioning
confidence: 99%
“…In the modified gravity theories, a particular invariant based on the contraction between the matter energy-momentum tensor and the Ricci tensor R µν T µν has been considered [43,61], taking into account a possible interplay between the space-time geometry and the fundamental characteristics of the matter component, embedded into the specific form of the energy-momentum tensor. From a theoretical perspective, such an approach is viable and can lead to different effects [62][63][64][65][66][67][68][69][70][71]. From this, the extension towards an invariant based on the interplay between the Einstein tensor and the energy-momentum tensor occurs naturally [72] and can lead to a viable modified gravity theory.…”
Section: Introductionmentioning
confidence: 99%